Daily Activities of Eclectus parrot (Eclectus roratus) at Ragunan Wildlife Park - Istiana, Rita; Saputri, Dina Dyah; Shity Muzdhalifah (Universitas Ahmad Dahlan, 2025)
This study examines the impact of the Augmented Reality (AR)-based Quantum Teaching model on high school students’ critical thinking and metacognitive skills in biology. As 21st-century education increasingly demands higher-order thinking, there is a growing need for innovative teaching approaches that foster these skills. The aim of this research was to determine whether combining AR technology with the Quantum Teaching model could enhance students’ cognitive and self-regulatory abilities. The study used a quasi-experimental pre-test post-test control group design, involving grade XI biology students at Pakusari State High School during the 2023/2024 academic year. Class XI-5 was randomly assigned as the experimental group and XI-4 as the control group. Data collection methods included observations, interviews, essay tests, and documentation, while data analysis was conducted using ANCOVA in SPSS version 26. The results showed that the experimental group experienced significantly greater improvements in both critical thinking and metacognitive skills compared to the control group. These findings suggest that the AR-based Quantum Teaching model effectively supports the development of essential academic competencies. The study concludes that integrating AR into student-centered teaching models not only enhances engagement but also promotes deeper learning. As a result, educators are encouraged to adopt AR-supported pedagogies, and schools should invest in digital infrastructure and teacher training to ensure successful implementation. The implications also extend to curriculum development, highlighting the potential of combining interactive technology with innovative instructional strategies to better prepare students for academic success and future challenges.